Protein arginine methyltransferase 3 inhibits renal tubulointerstitial fibrosis through asymmetric dimethylarginine - Wang, Yanzhe; Wu, Ming; Yang, Feng; Lin, Junyan; Zhang, Li; Yuan, Meijie; Chen, Dongping; Tan, Bo; Huang, Di; Ye, Chaoyang (Frontiers in Medicine, 2022)
Mammalian Protein Arginine Methyltransferase 3 (PRMT3) catalyzes the monomethylation and dimethylation of the arginine residues of proteins. The role of PRMT3 in renal fibrosis is currently unknown. We aimed to study the role of PRMT3 in renal fibrosis and explored its underlying mechanisms. Quantitative PCR analysis and Western blotting analysis showed that the expression of PRMT3 was up-regulated in unilateral ureteral obstruction (UUO) mouse kidneys. Knockout of Prmt3 gene enhanced interstitial fibrosis in UUO kidneys as shown by Masson staining and Western blotting analysis the expression of pro-fibrotic markers. The production of asymmetric dimethylarginine (ADMA) was increased in WT UUO kidneys but not further increased in Prmt3 knockout UUO kidneys. Administration of exogeneous ADMA in UUO kidneys blocked the enhanced renal interstitial fibrosis in Prmt3 mutant mice. Moreover, genetic deletion of Prmt3 gene increased blood urea nitrogen levels and renal deposition of collagen in folic acid injected mice. We conclude that PRMT3 inhibits renal tubulointerstitial fibrosis through elevating renal ADMA levels.